2018
DOI: 10.1007/s10103-018-2513-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser irradiation induces a transcriptional myotube-like profile in C2C12 myoblasts

Abstract: Low-level laser irradiation (LLLI) has been used as a non-invasive method to improve muscular regeneration capability. However, the molecular mechanisms by which LLLI exerts these effects remain largely unknown. Here, we described global gene expression profiling analysis in C2C12 myoblasts after LLLI that identified 514 differentially expressed genes (DEG). Gene ontology and pathway analysis of the DEG revealed transcripts among categories related to cell cycle, ribosome biogenesis, response to stress, cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…The combination of MB and LEDs (λ max = 660 nm) downregulated the expression of genes necessary for biofilm formation ( bsmA and bsmB ), attachment ( fimA a nd fimC ), motility ( flhD ) and QS regulation ( swrR ) in S. marcescens strains 45 . The downregulation of genes related to adherence ( als3 and hwp1 ), morphogenesis ( cph1 and efg1 ) and biofilm formation ( bcr1 and tec1 ) in C. albicans after aPDI treatment (MB with a red laser and erythrosine with an LED emitting green light) was demonstrated 43 . These observations confirmed the hypothesis that aPDI could effectively downregulate the expression of several virulence factors in various microbial species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The combination of MB and LEDs (λ max = 660 nm) downregulated the expression of genes necessary for biofilm formation ( bsmA and bsmB ), attachment ( fimA a nd fimC ), motility ( flhD ) and QS regulation ( swrR ) in S. marcescens strains 45 . The downregulation of genes related to adherence ( als3 and hwp1 ), morphogenesis ( cph1 and efg1 ) and biofilm formation ( bcr1 and tec1 ) in C. albicans after aPDI treatment (MB with a red laser and erythrosine with an LED emitting green light) was demonstrated 43 . These observations confirmed the hypothesis that aPDI could effectively downregulate the expression of several virulence factors in various microbial species.…”
Section: Discussionmentioning
confidence: 95%
“…Our observations were in line with those published by Freire et al . , in which other reference genes were stable in various photodynamic inactivation experiments in C. albicans 43 . This means that the stability of reference genes is strongly dependent on the experimental conditions and thus should be carefully analysed for specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LLLT has been shown to enhance mitochondrial biogenesis in polyploid megakaryocytes [18] and the expression of peroxisome proliferator-activated receptor-γ coactivator 1α (Pgc1a) in mouse muscle cells, a master regulatory gene for mitochondrial biogenesis [30]. Moreover, in a global transcriptome study, LLLT was found to upregulate a set of mRNAs that control myoblast differentiation into myotubes [31]. In contrast to the beneficial effect of LLL pre-conditioning, there was no measurable effect of LLL post-conditioning on myoblast differentiation under hypoxic conditions.…”
Section: Lll Pre-treatment Significantly Blunts a Metabolic Shift Tow...mentioning
confidence: 99%
“…SCs remain in a quiescent state between the basal lamina and sarcolemma in mature muscle fibers and are activated after an injury, initiating a proliferation process in which these cells are now denominated myoblasts. Myoblasts subsequently undergo an initial differentiation and fusion phase, uniting for the formation of multinucleated myotubes, which then fuse with the damaged muscle fibers or form new muscle fibers to promote regeneration [3,[6][7][8][9]. The C2C12 myoblast line is derived from mouse satellite cells and provides a good cellular model for studying the phases of myogenesis due to its capacity to proliferate and differentiate in a process similar to what occurs in vivo [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This noninvasive treatment modality consists of the application of light with a power output lower than 500 mW and a wavelength ranging from 400 to 1100 nm. The effects of this technique include the stimulation of tissue repair, analgesia, and a reduction in the inflammatory process, promoting the healing of injuries and preventing necrosis and tissue damage [7,8,10,[13][14][15]. In addition, da [7,10] used low-level laser (LLL) with different radiant exposure (10,35, and 70 J/cm 2 ) on C2C12 myoblasts, which are the same dosimetric parameters used in clinical protocols for treatment of muscle injury exposure and showed at low or high radiant exposure a stimulation in the elimination of non-viable cells by inflammatory machinery or the recovery of viable cells.…”
Section: Introductionmentioning
confidence: 99%